2003
DOI: 10.1159/000068199
|View full text |Cite
|
Sign up to set email alerts
|

Glare Disability and Driving Safety

Abstract: Purpose: Increasing investigation of the visual elements of safe driving environments may be of great benefit to society. Visual disability appears to be only one of many visual factors related to traffic accidents. The purpose of this article was to examine the type of visual impairment mediated by the increased glare sensitivity in adult drivers using the original halometer glare test. Methods: In this article, the visual sensory, cognitive and motor functions relevant to driving, their measurement, the epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…The authors concluded that a severe contrast sensitivity deficit due to cataract in even one eye increases the risk of at-fault crashes among older drivers. This finding is consistent with the suggestion that drivers with cataracts are at increased risk for nighttime accidents due to their greater vulnerability to glare, and that tests for glare sensitivity and/or contrast sensitivity might be helpful for assessing the magnitude of that risk (Babizhayev, 2003).…”
Section: Cataract and Drivingsupporting
confidence: 89%
“…The authors concluded that a severe contrast sensitivity deficit due to cataract in even one eye increases the risk of at-fault crashes among older drivers. This finding is consistent with the suggestion that drivers with cataracts are at increased risk for nighttime accidents due to their greater vulnerability to glare, and that tests for glare sensitivity and/or contrast sensitivity might be helpful for assessing the magnitude of that risk (Babizhayev, 2003).…”
Section: Cataract and Drivingsupporting
confidence: 89%
“…Mainly persons who are older than 50 years have a reduced visual acuity by glare conditions at night [3,43]. It can be due to flocculated particles in the vitreous body and increased lens density [27].…”
Section: Discussionmentioning
confidence: 99%
“…Most drivers are aware that approaching headlights or a low sun can make it more difficult to see objects outside their vehicle and some even avoid high-glare situations (Wolbarsht, 1977). Although it has been suggested that glare susceptibility testing might be used to identify drivers who are especially disabled by glare (Wolbarsht, 1977;Regan, 1991;Babizhayev, 2003), a causal connection between laboratory measures of an individual's glare susceptibility and the probability for accidents in high-glare conditions is lacking. It is even the case that the extent to which glare affects driving performance is not known: "Glare problems are often discussed as a serious threat to the safety of older drivers.…”
Section: Introductionmentioning
confidence: 99%
“…However, no studies have demonstrated that increased disability glare is independently associated with either crash involvement or self-reported difficulty in driving (pg. 21)" (Babizhayev, 2003). These are important gaps in our knowledge, given that a high level of glare susceptibility is common in older individuals (Allen, 1967;Regan, 1991), especially in those with early cataract (Miller & Benede, 1973;Regan, Giaschi & Fresco, 1993) and that it is projected that the proportion of drivers over the age of 65 will continue to increase over time to roughly 1 in 5 by the year 2030 (NHTSA, 2006).…”
Section: Introductionmentioning
confidence: 99%